Pemetaan Rawan Fenomena Sinkhole Sebagai Upaya Mitigasi Bencana Di Desa Lebbo Tengae, Kabupaten Maros - Ardianto Ardianto; Rihan Muhammad Alghifari; Nurul Hidayah (Geosfera: Jurnal Penelitian Geografi, 2025)
This study aims to determine the Sinkhole prone zone around the impact of the Sinkhole in Lebbo Tengae Village, Maros Regency by using this type of quantitative research and using a pure experimental approach. The data collection technique used was direct observation and measurement of the resistivity value of the rock under the surface around the Sinkhole. The results of the study revealed that the cause of the Sinkhole in Lebbo Tengan Village, Maros Regency was due to the presence of an aquifer below the surface that is right parallel to the Sinkhole. In addition, it was also found that the subsurface structure that made up the area was dominated by clay and sandy soil so that it was very easy to dissolve in aquifers. Based on the results of the research, there were suggestions especially for the community not to build buildings around the Sinkhole because of the active aquifer below the surface so that it has the potential for a Sinkhole to occur in the future